Development of antibiotic resistome in premature infants - Ayya Keshet; Ori Hochwald; Amit Lavon; Liron Borenstein-Levin; Saar Shoer; Anastasia Godneva; Yitav Glantz-Gashai; Noa Cohen-Dolev; Fanny Timstut; Maya Lotan-Pompan; Ido Solt; Adina Weinberger; et al. (Cell Reports)
Summary: Preterm birth is a major concern in neonatal care, significantly impacting infant survival and long-term health. The gut microbiome, essential for infant development, often becomes imbalanced in preterm infants, making it crucial to understand the effects of antibiotics on its development. Our study analyzed weekly, 6-month, and 1-year stool samples from 100 preterm infants, correlating clinical data on antibiotic use and feeding patterns. Comparing infants who received no antibiotics with those given empirical post-birth treatment, we observed notable alterations in the gut microbiome’s composition and an increase in antibiotic resistance gene abundance early in life. Although these effects diminished over time, their long-term clinical impacts remain unclear. Human milk feeding was associated with beneficial microbiota like Actinobacteriota and reduced antibiotic resistance genes, underscoring its protective role. This highlights the importance of judicious antibiotic use and promoting human milk to foster a healthy gut microbiome in preterm infants.